TRP channels as sensors and signal integrators of redox status changes - Nobuaki eTakahashi; Yasuo eMori (Frontiers Media S.A., 2011)
Proteins are capable of sensing the redox status of cells. Cysteine residues, which react with oxidants, reductants, and electrophiles, have been increasingly recognized as the mediators of this redox sensitivity. Cation channels encoded by the transient receptor potential (trp) gene superfamily are characterized by a wide variety of activation triggers that act from outside and inside the cell. Recent studies have revealed that a class of TRP channels is sensitive to changes in redox status and is notably susceptible to modifications of cysteine residues, such as oxidation, electrophilic reaction, and S-nitrosylation of sulfhydryls. In this review, we focus on TRP channels, which directly sense redox status, and discuss the biological significance of cysteine modifications and the consequences of this chemical reaction for physiological responses.